Scutellarin Inhibits Glioblastoma Growth in a Dose-dependent Manner by Suppressing the p63 Signaling Pathway - Yongjie Chen; Wenlan Li (SAGE Publishing, 2023)
Although scutellarin has been extensively investigated, its effects on glioma are unclear. This study intended to reveal this regulation and the underlying mechanisms. The U251, M059K, and SF-295 cell lines were treated with gradient concentrations of scutellarin and then IC 50 was calculated. SF-295 cells selected for subsequent procedures were treated with four concentrations of scutellarin. Then, proliferation, apoptosis, and cell cycle, as well as the protein and mRNA expression of significantly differentially expressed genes identified by next-generation sequencing (NGS), were examined. The curative effect of scutellarin was validated by 5-FU as the positive control. Scutellarin inhibited proliferation and induced apoptosis and G2/M cell cycle arrest in the SF-295 cell line in a dose-dependent manner. The effect of scutellarin was similar to but significantly weaker than the effect of 5-FU. The NGS results showed that genes associated with anti-apoptosis signaling pathways were significantly reduced after treatment. The Western blotting results indicated that the expressions of TP63/BIRC3/TRAF1/Bcl-2 were reduced in a dose-dependent manner, as well as the mRNA levels determined by qRT‒PCR. Our original conclusion revealed that scutellarin may inhibit glioma growth in a dose-dependent manner via the p63 signaling pathway which may provide a potential medicine for glioma chemotherapy.